Colonial Review of Mir and Ghalib’s Intellectual Perspectives - Sajid Naqvi, Syed Aoun; Abbas, Mujahid (sourcecoder, 2022)
Mir and Ghalib are the cultural metaphores of Urdu literature.Both have observed the downfall of Indian civilization during the colonial period of East India Compnay.They raised their poetic voices to explain the weeknesses of local political systems and dispersal of values in social setup. They have also recognized the evils in the minds of colonialists as they were planning for the cultural invasion of whole subcontinent. Mir has pessimistic approach in his poetry as he was observing the storm of darkness that was about to prevail everywhere. So, he has found only one way to save his identity by hiding his selfness in Sufism. It can be said that Mir has handed over his identity to the super power of the nature and this was the uncounsious reaction of his intellect. On the other hand, Ghalib has observed this invasion with his eyes. He has written many stories in his letters. His intellect was one step ahead from the Mir as he has not given up his identity till the end. He has taken the support of the Sufism and super power of the nature, but he has kept his intellect as his separate identity. In this article, it is tried to differniate the pattern of feelings of both classic figures Mir and Ghalib with reference to the colonial aspects.